Pengimplementasian Perkantoran Modern di Madrasah Tsanawiyah Al-Wasliyah Tembung - Rangga Hasibuan; Isnaini Sapitri Br Purba; Saila Rahma Nasution (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to evaluate the implementation of modern office practices at Madrasah Tsanawiyah Al-Wasliyah Tembung, encompassing staff training, procurement of hardware and infrastructure, document digitization, system integration, and the application of technology-based communication systems. A qualitative approach using a case study method was employed to gain an in-depth understanding of the processes and outcomes of the implementation. Data were collected through in-depth interviews, direct observations, and document analysis. The study also identifies the challenges faced, such as resistance to change and technical issues, and the strategies used to address them. The study concludes that the implementation of modern office practices significantly impacts the efficiency and effectiveness of madrasah operations and enhances the quality of educational services. This study recommends continuous staff training, investment in hardware and infrastructure, and a focus on document digitization and system integration for the successful implementation of modern office practices in other educational institutions.